Pemahaman Hadis-Hadis Terkait Niqab: Studi Atas Kitab Al-Niqāb Ādah Wa Laisa Ibādah - Mi'raj, Muhammad (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2021)
The phenomenon of the niqab, or face veil, is no longer unfamiliar among Indonesian women, particularly in urban areas. Public responses vary, ranging from acceptance to rejection. Discussions on the niqab have expanded, especially in Arab regions, where it is often associated with cultural and religious dimensions. Mahmoud Zaqzouq, in his work Al-Niqab ‘Adah wa Laisa ‘Ibadah, argues that the niqab is a cultural tradition rather than a form of worship. This study aims to: (1) examine the use of hadiths related to the niqab in Al-Niqab ‘Adah wa Laisa ‘Ibadah (2) explore Zaqzouq's interpretation of niqab-related hadiths, and (3) investigate scholarly debates surrounding his views. The research adopts a qualitative descriptive approach, utilizing library research and inductive-deductive analysis. Data were collected from Zaqzouq’s primary text and relevant secondary sources. The findings reveal that the hadiths presented in the book emphasize that wearing the niqab is not obligatory. They focus on the definition of female aurah which particularly during prayer includes the entire body except the face and hands. Zaqzouq contends that neither Islamic texts nor rational reasoning obligate women to wear the niqab, and therefore it cannot be considered an act of worship. His view has sparked both support and opposition: some scholars see the niqab as a pre-Islamic cultural practice, while others regard it as a valid religious obligation.